Ex situ Synthesis and Characterization of High Strength Multipurpose Bacterial Cellulose-Aloe vera Hydrogels - Ul-Islam, Mazhar; Ahmad, Furqan; Fatima, Atiya; Shah, Nasrullah; Yasir, Somayia; Ahmad, Md. Wasi; Manan, Sehrish; Ullah, Muhammad Wajid (Frontiers in Bioengineering and Biotechnology, 2021)
The innate structural and functional properties of bacterial cellulose (BC) have been greatly improved by developing its composites with other materials for its applications in different fields. In the present study, BC-Aloe vera (BCA) gel composite with high tensile strength was ex situ developed and characterized for its potential applications in environmental and medical fields. FE-SEM micrographs showed the impregnation of Aloe vera gel into the fibril network of BC. The dry weight analysis showed the addition of 40 wt.% Aloe vera contents into the BC matrix. The addition of Aloe vera resulted in a three-fold increase in the mechanical strength of BCA composite. The critical strain or stress concentration points were accurately identified in the composite using a three-dimensional digital image correlation (3D-DIC) system. The BCA composite retained water for an extended period of up to 70 h. The BCA composite effectively adsorbed Cu, Co, Fe, and Zn metals. Moreover, the BCA composite supported the adhesion and proliferation of MC3T3-E1 cells. The findings of this study suggest that the developed BCA composite could find multipurpose applications in different fields.